TV shows and nonplace why The Sopranos, Breaking Bad and co. love the periphery - Gutzmer, Alexander (Routledge focus on television studies, 2024)
This book scrutinizes the relationship between contemporary TV shows and space, focusing on the ways in which these shows use and narrate specific spatial structures, namely, spaces far away from traditional metropolises.Beginning with the observation that many shows are set in specific spatial settings, referred to in the book as "nonplace territories" – e.g., North Jersey, New Mexico, or rural and suburban Western Germany – the author argues that the link between such nonplace territories and shows such as The Sopranos, Breaking Bad, or Dark is so intense because the narrative structure functions similarly to these territories: flat, decentralized, without any sense of structure or stable hierarchy. The book takes three different perspectives: first, it looks at the rationale for combining TV shows and nonplace territories from the viewpoint of narrative strategy. It then thinks through what these strategies mean for practicing architects. Finally, it approaches the arguments made before from a "user" perspective: what does this narrative mirroring of social-spatial reality in places such as Albuquerque or Jersey City mean for people living in these places?This new approach to architecture and space on screen will interest scholars and students of television studies, screen architecture, media and architectural theory, and popular culture